What makes a parent in surrogacy cases? Reflections on the Fjölnisdóttir et al. v. Iceland decision of the European Court of Human Rights. (September 2021) - März, Julian W
The present commentary analyses and discusses the Fjölnisdóttir et al. v. Iceland decision of the European Court of Human Rights (ECtHR) of 18 May 2021. The case concerned an Icelandic couple who had been recognised as the legal parents of a child born by a surrogate mother in California. In contrast to most other surrogacy cases decided by the ECtHR, however, the child had no biological link to either of the intended parents. The ECtHR thus found that a ruling of the Supreme Court of Iceland which had rejected the recognition of the legal parenthood of the intended parents under Icelandic law had not violated Art. 8 of the European Convention on Human Rights, despite the fact that joint adoption by the intended parents was not possible in this case. The present commentary argues that this decision exaggerates the importance of the biological link, creating injustices at the expense of the child concerned. In conclusion, the commentary calls for a more consistent and holistic framework to protect the best interests of the child and to prevent abuses of transnational commercial surrogacy.